2015
DOI: 10.1021/acs.orglett.5b02044
|View full text |Cite
|
Sign up to set email alerts
|

Two Pairs of Enantiomeric Alkaloid Dimers from Macleaya cordata

Abstract: Two pairs of enantiomeric alkaloid dimers, (±)-macleayins A (1) and B (2), representing a novel dimerization pattern of two different types of alkaloids via a C-C σ-bond, were isolated from the aerial parts of Macleaya cordata. The enantiomeric separation was achieved by chiral chromatography. Their structures and stereochemistry were determined by the analysis of extensive spectroscopic data, electronic circular dichroism calculation, and single-crystal X-ray diffraction data. (-)-Macleayin A exhibits modest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…1 and 2. These compositions are summarized along with their retention time, theoretical mass, molecular formula, observed mass, error and MS/MS fragments combined with literature reports [15,16] and previously isolated alkaloids from M. cordata [7,9,17,18]. A total of 14 possible alkaloids have been identified, of which 9 are known.…”
Section: Analysis Of Alkaloids From Fruits Of M Microcarpa By Uhplc-mentioning
confidence: 97%
See 1 more Smart Citation
“…1 and 2. These compositions are summarized along with their retention time, theoretical mass, molecular formula, observed mass, error and MS/MS fragments combined with literature reports [15,16] and previously isolated alkaloids from M. cordata [7,9,17,18]. A total of 14 possible alkaloids have been identified, of which 9 are known.…”
Section: Analysis Of Alkaloids From Fruits Of M Microcarpa By Uhplc-mentioning
confidence: 97%
“…The method can provide high resolution and accuracy data, as well as abundant structural information such as high-resolution second-stage mass fragment ions [5,6]. This study aimed to rapidly and conveniently characterize alkaloids from M. microcarpa by UHPLC-Q-TOF-MS using accurate mass weight and characteristic fragment ions, furthermore separate and identify the main alkaloids by chromatographic and spectral techniques, test antitumor activity in vitro using the trypan blue method and MTT method reported previously [7], and antiangiogenic activity in vivo using transgenic zebrafish [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that quaternary benzo[c]phenanthridine alkaloids such as sanguinarine ( 11 a ) could produce architecturally intriguing alkaloids coupled with protopine alkaloid (Figure ). In 2015, Hua and co‐workers have reported two pairs of enantiomeric alkaloid dimers, (±)‐macleayins A ( 15 a ) and B ( 15 c ), from the aerial parts of Macleaya cordata . These alkaloids represent.…”
Section: Structure Of Hybrid Benzo[c]phenanthridine Alkaloidsmentioning
confidence: 99%
“…Totally, 62 dihydrobenzophenanthridine alkaloids ( 38–99 ) were found in Macleaya species. Most of them are monomeric but interestingly, Sai et al () have isolated five pairs of new enantiomeric natural alkaloids (±)‐macleayins A‐E ( 91–95 ) from the aerial parts of M. cordata .…”
Section: Phytochemistrymentioning
confidence: 99%